The Graphene Oxide Spincoating Optimalization by Planned Experiment - Zahradnicek, Radim; Prokes, Tomas; Benes, Libor (Manufacturing Technology Journal, 2017)
Spin coating is basic method for preparation of thin polymer resist layer (polycarbonate) or colloidal solution (grapheme oxide in alcohol). This method main benefits are speed of preparation and the possibility of tuning final coating of silicon sample by variations of parameters such as the speed of rotation, time and the amount of the solution. To find out the exact graphene oxide layer spin coating process a planned experiment was designed. The greatest coverage of the silicon sample grapheme was obtained by studying the data obtained from electron microscopy (SEM) and light microscopy (LM) of the spin coating input conditions
Keywords: Graphene oxide; spin coating; Design of Experiment; Analysis of Variance; response surface